(untitled) (Annals of Medical Research, 2025)
Aim: Unplanned readmissions to the intensive care unit (ICU) are associated with poor clinical outcomes, prolonged hospital stays, and increased healthcare costs. Identifying the clinical and laboratory predictors of ICU readmission and its impact on in-hospital mortality remains critical for improving patient safety and optimizing utilization of the resources. This study aimed to investigate the factors associated with ICU readmission and evaluate its relationship with mortality in a tertiary-care hospital setting. Materials and Methods: In this retrospective cohort study, data of 1347 patients followed in Pulmonary ICU between 2016 and 2024 were retrospectively evaluated. Data of 153 patients (75 patients readmitted and 78 control cases selected randomly who were not readmitted during the same hospitalization) were analyzed. The two groups -those with and without ICU readmission- were compared in terms of demographic characteristics, clinical parameters, comorbidities, nutritional status, and laboratory findings. Logistic regression analysis was used to identify predictors of mortality. Results: Readmitted patients were older (p=0.001), had lower Glasgow Coma Scores (p <0.001), higher APACHE II scores (p <0.001), and longer ICU and hospital stays (p=0.002, p=0.006 respectively). They also required more vasopressors (p=0.004), mechanical ventilation (p=0.001), and sedation (p<0.001). Nosocomial infections were more frequent in this group (p <0.001). Univariate regression analysis revealed that ICU readmission, low serum albumin, nosocomial infections, use of vasopressors, and comorbidities such as dementia and cerebrovascular disease were significantly associated with mortality (p<0.05). In the Backward Wald model, albumin during hospitalization, nosocomial infection and APACHE II scores were independent risk factors for mortality (p<0.05). Conclusion: ICU readmission is strongly associated with adverse clinical outcomes and increased in-hospital mortality. Identifying high-risk patients based on clinical and laboratory parameters—such as low serum albumin levels, presence of nosocomial infections, use of vasopressors, and comorbidities like dementia/Alzhiemer’s disease—may facilitate early interventions and improve patient prognosis.